Uncertainty analysis of IceCube instrument to enhance accuracy of specific surface area measurements - Leppänen, Leena (Elsevier, 2025)
The specific surface area (SSA) is a measure of the snow microstructure and can be determined using an instrument called IceCube. IceCube measures the reflectance from surface of a snow sample with a 1310 nm infrared laser. In this study, the uncertainties associated with IceCube measurements of SSA were analyzed in two locations: Sodankylä, Finland and Queen Maud Land, Antarctica. The study tests the repeatability of the measurements by measuring several samples from the same height of a homogenous snowpack. Additionally, snow samples were rotated to find minimum and maximum reflectance values to test the uncertainty related to the direction of the sample under the laser. The study also observed the uncertainty related to potential melting of the sample in warm conditions due to slow measurement process. The study resulted that the highest uncertainty is related to the sampling process. Overall, this study provides insights into the uncertainties associated with IceCube measurements of SSA, which will improve the precision and reliability of future measurements.